Synthesis of some α,-unsaturated ketones from 3-acetyl-6-hydroxy-4-methylcoumarin - Thanh, Nguyen Ngoc; Thao, Nguyen Minh; Bich Ngoc, Dao Thi (Vietnam Journal of Chemistry, 2012)
By cyclization reaction of 2,5-dihydroxyacetophenone with ethyl acetoacetate to get 3-acetyl-6-hydroxy-4-methylcoumarin). The product was then transformed by condensation with aromatic aldehydes to form a series of new α,β-unsaturated ketones (6 compounds) and (4-arylvinyl-6-hydroxycoumarin-3-yl) arylvinyl ketones (4 compounds) and (6-hydroxy-4-methylcoumarin-3-yl) (2,3-dihydrobenzofur-2-yl) ketone. Structure of the obtained products was determined by IR, 1H-NMR, and MS spectroscopic data.